Protease inhibitors in potatoes resistant and susceptible to leaf the miner fly Liriomyza huidobrensis (Diptera:Agromyzidae) - OLIVERA, JOSÉ; PALACIOS, MARÍA; TENORIO, JORGE; MARCELO, ÁLVARO; GOLMIRZAIE, ALÍ (Revista Colombiana de Entomología, 2007)
Abstract Biochemical differences were studied among five potato clones: four resistant (220LM87B, 662LM86B, 136LM86B and cultivar María Tambeña) and one susceptible (cultivar Revolución) to attack of the leafminer fly Liriomyza huidobrensis (Diptera, Agromyzidae) through a comparison of the degree of inhibition of the proteolytic activity of synthetic trypsin and extracts of leafminer larvae by action of total proteins extracted from the leaves of the different potato clones before damage. The proteolytic activity, in relative units, of the clones 662LM86B, 136LM86B, 220LM87B, María Tambeña, and Revolution on trypsin activity were 1.7, 2.5, 1.8, 1.3, and 2.4, and on larval extracts were 0.24, 0.4, 0.6, 0.1 and 0.5, respectively. In contrast, when inhibition of the proteolytic activity of trypsin from proteins of the cultivars María Tambeña and Revolución was quantified, there was an inhibition of 93% and 77%, respectively. Finally, using zymography, two bands of protease inhibitors were identified, one 105 kDa and the other 63 kDa; the degree of intensity of these bands was greater in the resistant clones than the susceptible. The 105 kDa band showed an intensity up to 4.2 times higher in the cultivar María Tambeña than the cultivar Revolución. The results demonstrate differences in the proteolytic activity and the presence of the 105 kDa band between the clones resistant and susceptible to the leafminer fly, which suggests that protease inhibitors are important factors in the resistance of these clones to the leafminer fly.